Penurunan Surface Roughness Hasil Pembubutan Rata Baja ST 42 Akibat Pengaruh Variasi Sudut Potong Pahat Dan Kecepatan Spindle Mesin Bubut - I Gede Wiratmaja; I Nyoman Pasek Nugraha; I Gede Ari Saputra (LPPM Politeknik Jambi, 2023)
The purpose of this study was to determine the ratio of surface roughness in ST 42 steel with cutting angles of , , and at speeds of 490 Rpm and 700 Rpm. This method uses an experimental method with independent variables, namely cutting angle and spindle speed and bound variables, namely surface roughness in ST 42 steel. To test the surface roughness results using the surface roughness tester tool, which obtained the average value of surface roughness at a tool cutting angle of with a speed of 490 Rpm of 2.848 μm, a cutting angle of of 2.530 μm and a cutting angle of of 2.423 μm. At a speed of 700 Rpm at a cutting angle of of 2.439 μm, a cutting angle of of 2.179 μm and a cutting angle of of 2.048 μm. From these data, it can be concluded that there is an influence on the variation of the cutting angle of the lathe tool and spindle speed on the surface roughness value of steel ST 42.Where at the spindle speed of the lathe 700 Rpm at the cutting angle of the lowest surface roughness value is obtained